Strategi Dan Tantangan Membangun Jiwa Entrepreneurship Pada Peserta Didik Di SMK Al-Ishlah Cikarang Utara - Satim Hamid; Jon Edy; Rachmat Ramadhani; Erna Nur Ifah; Amin Amin; Anton Cahyono; Fahmi Najib; Tiwi Ayu Lestari (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Entrepreneurship is the ability to perform creativity and innovation that creates a work of value that can be sold. The limited job market is a classic problem that has not yet been resolved due to the continuously increasing population and the scarcity of jobs, thus the unemployment rate in the country continues to increase. Therefore, it is necessary to provide knowledge about entrepreneurship from school. Students at SMK Al-Ishlah North Cikarang are Generation Z, class XII, who will face graduation and thus will determine the next step, whether to look for a job, continue to higher education or start a business. These students should not be confused about what to do after graduation. This Community Service activity takes the theme "Fostering Entrepreneurial Spirit among Students: Strategies and Challenges in Building Entrepreneurship in the World of Education". It is carried out by seminar method which besides material presentation also includes discussion and question and answer session with the speaker. This activity was attended by as many as 43 participants, all of whom were class XII. Based on a survey from participants, it can be known that 63% strongly agree that this seminar has added their insight into entrepreneurship.